Evaluating of effects for the sequence fermentation with M. pulcherrima and I. terricola on mulberry wine fermentation: Physicochemical, flavonoids, and volatiles profiles - Haotian Xu; Zeyu Wang; Zhenyang Qin; Minwei Zhang; Yanan Qin (Food Chemistry: X)
This study investigates the variation of physicochemical, flavonoids, and volatiles during sequential fermentation which Metschnikowia pulcherrima and Issatchenkia terricola as sequential co-fermenters and a single fermentation by Saccharomyces cerevisiae in mulberry wine. Sequential fermentation shown that β-glucosidase activity greater and fermentation time declined to 144 h. In addition, 11 flavonoids (apigenin-5-O-glucoside, aromadendrin-7-O-glucoside, kaempferol-3,7-O-diglucoside, and so on) were significantly increased. Significant differences were found between types of metabolic products enriched in flavone and flavonol biosynthesis and anthocyanins biosynthesis, with an enrichment ratio of 46.15 % and 23.08 %, respectively. 16 apple-scented compounds (2-Buten-1-one, (E)-1-(2,6,6-trimethyl-1,3-cyclohexadien-1-yl)-, Butanoic acid, (Z)-3-hexenyl ester, 3-methyl-1-methylethyl-Butanoic acid ester, and so on), 5 rose-scented (e.g. benzyl alcohol, ethyl geranate, hydrocinnamic acid), and 4 balsamic-scented compounds ((−)-myrtenol, benzoic acid 1-methylethyl ester, benzyl alcohol, p-cymen-7-ol) were distinctively present. Interestingly, tryptophan metabolism and indole alkaloid biosynthesis are only enriched in sequential fermentation.